2009
DOI: 10.1111/j.1742-1241.2008.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 is not effective in the treatment of chronic chilblains

Abstract: Oral administration of 2000 IU vitamin D3 per day is not better than placebo in the treatment of patients with chronic chilblains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…In an earlier study on the effectiveness of vitamin D3 with 33 participants recruited in a similar way, two of the current authors observed a baseline VOC of 27.97 mm (standard deviation [SD] 18.82). 5 An estimate was used of the correlation between two VAS scores from the same individual on two occasions of 0.5. Treatment effect was considered to be clinically relevant in the case of a 10 mm decrease in the VOC.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study on the effectiveness of vitamin D3 with 33 participants recruited in a similar way, two of the current authors observed a baseline VOC of 27.97 mm (standard deviation [SD] 18.82). 5 An estimate was used of the correlation between two VAS scores from the same individual on two occasions of 0.5. Treatment effect was considered to be clinically relevant in the case of a 10 mm decrease in the VOC.…”
Section: Sample Sizementioning
confidence: 99%
“…1,7 The validity of the confirmation of the diagnosis had previously been demonstrated. 5 The authors excluded people with a known rheumatic disorder (for example, rheumatoid arthritis or systemic lupus erythematosus), those who were using nifedipine or other calcium antagonist, those who had been using a corticosteroidcontaining cream in the previous 4 weeks, and females who were pregnant or lactating.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In an earlier study, we found that vitamin D 3 was not superior to placebo, however. 5 Five studies evaluating the effectiveness of nifedipine in patients with chilblains have been published and have concluded that the drug is an effective treatment. These studies included only 1 randomized controlled trial, having 10 patients and conducted in 1989, compared nifedipine with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…We used an estimate of 0.5 for the correlation between 2 scores from the same patient on 2 occasions. 5 We considered the treatment effect to be clinically relevant if patients experienced a decrease in the VOC score of at least 10 mm.On the basis of use of a t test for the difference between 2 dependent means, 1-tail testing, an α of 0.05, and a β of 0.10 (power of 90%), we calculated that we would need a minimum of 32 participants for the trial. …”
mentioning
confidence: 99%
See 1 more Smart Citation